“The Earth is Our Mother”: Freedom of Religion and the Preservation of Indigenous Sacred Sites in Canada - Bakht, Natasha; Collins, Lynda (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2017)
For centuries, the Canadian state engaged in systematic religious persecution of Indigenous peoples through legal prohibitions, coercive residential schooling, and the dispossession and destruction of sacred sites. Though the Canadian government has abandoned the criminalization of Indigenous religious practices and is beginning to come to grips with the devastating legacy of residential schools, it continues to permit the destruction and desecration of Indigenous sacred sites. Sacred sites play a crucial role in most Indigenous cosmologies and communities; they are as necessary to Indigenous religions as human-made places of worship are to other religious traditions. The ongoing case of Ktunaxa Nation v. British Columbia (Forests, Lands and Natural Resource Operations) represents the first opportunity for the Supreme Court of Canada to consider whether the destruction of an Indigenous sacred site constitutes a violation of freedom of religion under subsection 2(a) of the Canadian Charter of Rights and Freedoms. Building on the ground-breaking work of John Borrows and Sarah Morales, we will argue that Indigenous spiritual traditions have a home in this provision and merit a level of protection equal to that enjoyed by other faith groups in Canada. In general, subsection 2(a) will be infringed by non-trivial state (or state-sponsored) interference with an Indigenous sacred site. Moreover, the approval of commercial or industrial development on an Indigenous sacred site without consent and compensation will generally be unjustifiable under section 1 of the Charter. Recognition of these principles would signal respect for the equal religious citizenship of Indigenous Canadians.